Pembaruan Metode Penemuan Hukum Islam: Pendekatan Terpadu Hukum Islam dan Sosial - Moh. Lutfi Nurcahyono (Ulumuna, 2012)
The shifting of islamic law/fiqh thought from orthodoxy-truth-based paradigm to social-meaning-based one, or from a “black-white” character to be a “nuanced” as well as rich perspective describes the flexibility of progress experienced by Islamic law. Such a change (al-tagayyur) is a necessity and a logical consequence of its flexibility character. Further consequence is the necessity of continuing efforts to do the excavation, discovery, customization, and filtering of the change. This article aims to explore one of the efforts, namely the renewing of method of Islamic law invention, especially in this era, in the form of an integrated approach to Islamic law and social sciences.